Melatonin attenuates ifosfamide-induced Fanconi syndrome in rats - (:unkn) unknown (WILEY-BLACKWELL, 2004)
Regarding the mechanisms of ifosfamide (IFO)-induced nephrotoxicity and hemorrhagic cystitis, several hypotheses have been put forward, among which oxidative stress and depletion of glutathione (GSH) are suggested. This investigation elucidates the role of free radicals in IFO-induced toxicity and the protection by melatonin. Wistar albino rats were injected intraperitoneally with saline (0.9% NaCl; control-C group), melatonin (Mel group; 10 mg/kg daily for 5 days) or ifosfamide (50 mg/kg daily for 5 days; IFO group) or IFO + Mel. On the 5th day (120 hr) after the first IFO dose, animals were killed by decapitation and trunk blood was collected. Kidney and bladder tissues were obtained for biochemical and histological analysis. Urine was collected 24 hr before the rats were killed. The results demonstrated that IFO induced a Fanconi syndrome (FS) characterized by wasting of sodium, phosphate, and glucose, along with increased serum creatinine and urea. Melatonin markedly ameliorated the severity of renal dysfunction induced by IFO with a significant decrease in urinary sodium, phosphate, and glucose and increased creatinine excretion. Moreover, melatonin significantly improved the IFO-induced GSH depletion, malondialdehayde accumulation and neutrophil infiltration in both renal and bladder tissues. In the kidney, Na(+),K(+)-ATPase activity which was significantly reduced by IFO, was increased with melatonin treatment. Increased collagen contents of the kidney and bladder tissues by IFO treatment were reversed back to the control levels with melatonin. Our results suggest that IFO causes oxidative damage in renal and bladder tissues and melatonin, via its antioxidant effects, protects these tissues. These data suggest that melatonin may be of therapeutic use in preventing acquired FS due to IFO toxicity.
Keywords: collagen; glutathione; ifosfamide; myclo; melatonin; Na(+),K(+)-ATPase; METABOLITE CHLOROACETALDEHYDE; ANTITUMOR-ACTIVITY; OXIDATIVE STRESS; TUBULE CELLS; IN-VIVO; KIDNEY; MESNA; NEPHROTOXICITY; GLUTATHIONE; SERUM